The Relationship between Sex Education and Sexual Behaviour in Adolescents - Nofi Susanti; Reinpal Falefi; Tri Bayu Purnama (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Adolescent sexual behavior remains a global problem with high reports of cases of adolescents behaving freely. The lack of knowledge about sexuality is caused by limited information, services, and advocacy. There has not been a reproductive health curriculum for adolescents in schools. Therefore, this study aims to determine the relationship between sex education and sexual behavior in adolescents. This research is a quantitative study with a cross-sectional design. The sampling was taken using a total sampling technique. The sample included all students of class X and XI, with a total of 102 people. The research instrument used a questionnaire. Data were analyzed using chi-square and multiple logistic regression. Bivariate analysis results showed that there was a relationship between sex education by parents, teachers, peers, and social media and sexual behavior. The results of multivariate analysis with logistic regression tests showed that sex education provided by parents was the most substantial relationship with sexual behavior. The study concluded that parents, teachers, and social media were associated with sex education. Extensive sex education from other trusted information could reduce pre-marital sexual activity among adolescents.  Elaborating on external factors would implicate a good attitude and behavior in students.